Synonymy and Its Synonyms - Виноградов, М. Ф. (Kalbotyra, 1992)
A set of terms to denote synonymity in natural language is dependent on interpretation of nature and character of meaning equivalence between language units. Its heterogeneity allows to argue that synonymity in its traditional sense is confined only to a definite type of equivalence. In other words, there are no synonyms of the term “synonymy”.